Pemenuhan Kebutuhan Lanjut Usia Di Desa Cisalak Kecamatan Cisarua Kabupaten Sumedang: Pemenuhan Kebutuhan Lanjut Usia di Desa Cisalak Kecamatan Cisarua Kabupaten Sumedang - Eling Gusti, Alif; Pribowo, Pribowo; Widiansyah, Wiwit (Pekerjaan Sosial, 2025)
Fulfilling the needs of the elderly is an effort to prevent the emergence of elderly-related problems. This study aims to examine the fulfillment of the needs of the elderly in Cisalak Village, Cisarua District, Sumedang Regency. In addition, this study aims to identify potential improvements in meeting the needs of the elderly at the village level. The research method used is descriptive qualitative with a survey approach. The research sample involved elderly individuals who were willing and able to become informants, as well as alternative informants from the families of the elderly in Cisalak Village. Data was collected through structured interviews and observations, and analyzed using qualitative data analysis. The results of the study show that the elderly in Cisalak Village are able to meet their physiological needs, safety and security needs, love and belonging needs, and esteem needs well. However, the elderly have not been able to adequately fulfill their self-actualization needs. Despite having a lot of time, they have not been able to utilize their abilities well. In addition, the elderly are less involved in community activities. Therefore, a program called Gali Lantera (Caring Families for Elderly Welfare) has been formulated, designed to involve the elderly in posbindu activities and provide counseling to the families of the elderly about fulfilling the needs of the elderly.